(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Many applications that use wireless sensors rely on data collected by sensors in the field. Sensor nodes have been charged with continuously relaying data to storage nodes throughout the applications we’ve described thus far. It is critical to update the Top-K rule, which is in charge of making predictions, with new data. The system administrators purposefully lied about the original content details in order to prevent unauthorized users from accessing the information they sought. After it became evident that the sensors and storage devices had been compromised and were being utilized by attackers, these safeguards were implemented. If hostile actors manage to get past the storage node’s safeguards, they may be able to deliver faked data to the control system. When steganography is used with the add-up complete signature method, the integrity of the delivered message is ensured, guarding against faults in the current security system. Before data is sent to storage nodes, it is indexed to ensure that database entries have access to the resources they require